Pengaruh Posisi Head Up 30o Terhadap Post Operative Nausea and Vomiting Pada Pasien Post Spinal Anestesi di Recovery Room RSUD Mardi Waluyo Blitar - Bahrudin; Arif , Taufan; Ciptaningtyas, Maria Diah; Hidayah , Nurul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Postoperative Nausea and Vomiting (PONV) is a common complication in patients undergoing spinal anesthesia. One of the interventions to reduce PONV is the application of a 30° head-up position, while maintaining patients in the supine position after spinal anesthesia may lead to high spinal block. The head-up position utilizes gravity to suppress the gastroesophageal reflex that triggers PONV. This study aims to analyze the effect of a 30° head-up position on the reduction of PONV. Methods: The study employed a quasi-experimental design with a two-group pretest–posttest control group approach. The sample was obtained using a non-probability purposive sampling technique, involving 32 respondents divided into three groups. The inclusion criteria were postoperative spinal anesthesia patients experiencing moderate to severe PONV. The independent variable in this study was the 30° head-up position, while the dependent variable was the level of PONV. Data were collected using the RINVR observation sheet and analyzed with a paired-sample t-test. Ethical approval for this study was obtained from Mardi Waluyo General Hospital, Blitar. Results: The results of the paired t-test showed a decrease in the mean PONV scores between the pretest and posttest in the control group, from 3.55 to 1.88. In the 30° head-up intervention group, the mean PONV scores decreased from 6.13 to 1.25 between the pretest and posttest. Conclusion: The paired t-test analysis revealed that both groups demonstrated a significant difference between pretest and posttest PONV scores. The control group showed a reduction in mean PONV scores from 3.55 to 1.88, while the 30° head-up intervention group demonstrated a greater reduction, from 6.13 to 1.25. Both groups obtained a Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a statistically significant effect of the intervention. Accordingly, the research hypothesis (H1) was accepted.